N-Hexanal and (Z)-3-hexenal are generated from arachidonic acid and linolenic acid by a lipoxygenase in Marchantia polymorpha L. Issue 6 (3rd June 2017) - Tawfik, Moataz M.; Yamato, Katsuyuki T.; Kohchi, Takayuki; Koeduka, Takao; Matsui, Kenji
Abstract : Most terrestrial plants form green leaf volatiles (GLVs), which are mainly composed of six-carbon (C6) compounds. In our effort to study the distribution of the ability of lipoxygenase (LOX) to form GLVs, we found that a liverwort, Marchantia polymorpha, formed n -hexanal and ( Z )-3-hexenal. Some LOXs execute a secondary reaction to form short chain volatiles. One of the LOXs from M. polymorpha (MpLOX7) oxygenized arachidonic and α-linolenic acids at almost equivalent efficiency and formed C6-aldehydes during its catalysis; these are likely formed from hydroperoxides of arachidonic and α-linolenic acids, with a cleavage of the bond between carbon at the base of the hydroperoxy group and carbon of double bond, which is energetically unfavorable. These lines of evidence suggest that one of the LOXs in liverwort employs an unprecedented reaction to form C6 aldehydes as by-products of its reaction with fatty acid substrates. Graphical abstract: One of Marchantia polymorpha lipoxygenases forms six-carbon aldehydes as by-products.